The Effect of Utilizing Powtoon on EFL Junior High School Students’ Vocabulary Achievement - Aryasatya Putra Erdianto (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
In the context of the contemporary globalized world, the possession of a sufficient vocabulary is a fundamental aspect of language proficiency and communication skills. Adequate vocabulary enables the current generation of students, particularly Generation Z, to express their thoughts, ideas, and opinions fluently, precisely, and appropriately across various communicative situations and contexts (Warschauer & Sykes, 2017). Furthermore, they agree that an adequate vocabulary is a transformative factor, serving as a foundation for proficiency in other language skills, such as speaking, reading, writing, and listening. Consequently, the current study aims to investigate the impact of Powtoon on English vocabulary achievement at different levels of proficiency. The study was conducted among eighth-grade English as a Foreign Language (EFL) junior high school students at one of the educational institutions in East Java, Indonesia. The rationale for this study is the absence of research investigating the utilization of Powtoon among EFL junior high school students. This quantitative research employed a quasi-experimental design; the researcher did not utilize random assignment. In quasi-experimental designs, an independent variable is manipulated, similar to experimental designs, although random assignment is not employed. Such designs are frequently employed in circumstances where randomization is not a viable option, enabling researchers to draw causal inferences while accounting for practical constraints (Creswell, 2014). The participants in this research were two classes of eighth-grade English as a Foreign Language (EFL) students from one of the junior high schools in Jember, Indonesia, during the 2023/2024 academic year. The participants used convenience sampling based on several factors such as the proximity of the class location to the language lab, the weekly class schedule, and the teacher’s recommendation. Subsequently, the participants were subjected to four sessions of treatments, after which a post-test was conducted on both the control and experimental classes. Upon completion of the research, the findings demonstrated that in the control group, the mean pre-test score of students was 76.02, whereas the Post-Test score was 78.52. In contrast, the average Pre-Test score of students in the experimental class using Powtoon was 78.33, while the Post-Test score was 83.70. The results obtained in both the control and experimental classes demonstrate that the Normalized Gain (N-Gain) score percentage increase in student learning outcomes in the control class was 57.52378%, and in the experimental class, it was 49.82519%. After hypothesis testing, the results yielded a P-value of 0.085, thereby indicating a rejection of the null hypothesis (H0). Consequently, it can be concluded that there is an effect on students’ English vocabulary achievement as a result of using Powtoon.
Reupload Repository 11 Februari 2026_Hasim/Firdiana
Keywords: Utilizing Powtoon; EFL; Vocabulary Achievement